Decision support system for superior livestock commodities in North Central Timor using Fuzzy Topsis method - Taek, Sisilia Novita Aryenny; Kelen, Yoseph Pius Kurniawan; Tey seran, Krisantus Junarto (Jurnal Simantec, 2025)
The livestock sector plays a crucial role in supporting regional economic development, including in North Central Timor (TTU) Regency, East Nusa Tenggara. Currently, the selection of superior livestock commodities in this area is still carried out manually, which results in slow, inefficient, and error-prone decision-making processes. Therefore, a system is needed to assist in making decisions more accurately and objectively. This study aims to develop a web-based Decision Support System (DSS) to analyze and determine superior livestock commodities in TTU Regency using the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) method. The system was developed using the Waterfall model and implemented with PHP and MySQL. The decision criteria include productivity, market potential, production cost, environmental sustainability, and infrastructure support. The livestock alternatives considered in the analysis are cattle, goats, pigs, chickens, sheep, and horses. The implementation results show that beef cattle achieved the highest preference score of 0.76, making it the most superior livestock commodity in the region. This system provides easy access to accurate and real-time data for users and facilitates more effective and efficient decision-making. It also minimizes human error and speeds up the analysis process. With this system, stakeholders and livestock-related agencies can make better-informed decisions, improve resource management, and support sustainable development in the local livestock sector.Keywords: Decision Support System, Leading Commodities, Livestock, Fuzzy TOPSIS